2017
DOI: 10.1016/j.jgeb.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

First study of sperm mediated gene transfer in Egyptian river buffalo

Abstract: The present study was carried out to find the best treatments for enhancing the ration of insertion of a desired gene construct (pEGFP-N1) onto the sperm of buffalo as the first step for the production of transgenic buffalo using sperm mediated gene transfer (SMGT). The tested conditions were plasmid DNA concentration, sperm concentration, transfecting agent concentration: Dimethyle sulphoxide (DMSO) and time of transfection. The study proved that the best conditions for producing transgenic embryos were incub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…The SMGT method has shown successful effectiveness in generating Tg farm animals, such as pigs (Chang et al., 2002), rabbits (Shen et al., 2006), cattle (Shemesh et al., 2000), goats (Ye et al., 2008), and sheep (Pereyra‐Bonnet et al., 2011). Several standard parameters contribute to the effectiveness of SMGT, including: (1) quality of the semen sample (volume, concentration, presence of sperm with abnormal morphology, and motility); (2) DNA uptake; (3) incubation media; and (4) the assisted reproductive technique used (Hassanane et al., 2017; Lavitrano et al., 2003). The SMGT method has advantages, including low cost, ease of use, high efficiency, DNA translation, DNA functionality, and DNA transfer to the next generation (Lavitrano et al., 2002).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The SMGT method has shown successful effectiveness in generating Tg farm animals, such as pigs (Chang et al., 2002), rabbits (Shen et al., 2006), cattle (Shemesh et al., 2000), goats (Ye et al., 2008), and sheep (Pereyra‐Bonnet et al., 2011). Several standard parameters contribute to the effectiveness of SMGT, including: (1) quality of the semen sample (volume, concentration, presence of sperm with abnormal morphology, and motility); (2) DNA uptake; (3) incubation media; and (4) the assisted reproductive technique used (Hassanane et al., 2017; Lavitrano et al., 2003). The SMGT method has advantages, including low cost, ease of use, high efficiency, DNA translation, DNA functionality, and DNA transfer to the next generation (Lavitrano et al., 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Hassanane et al. (2017), used DMSO to transfer the construct (pEGFP‐N1) onto the sperm of buffalo (SMGT), and the expression of GFP was observed in 74.2% of Blastocysts (Hassanane et al., 2017). In SMGT method, a study by Kurd et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that sperm isolated from the epididymis when incubated with a plasmid can transfer foreign DNA to oocytes (Brackett et al , 1971). Subsequently, SMGT in chickens (Nakanishi and Iritani, 1993), buffalo (Hassanane et al , 2017), pigs (Lavitrano et al , 2002) and zebrafish (Khoo, 2000) have been reported.…”
Section: Introductionmentioning
confidence: 99%